Ursachen vorzeitiger Vertragslösungen im Spannungsfeld von statistischer Beschreibung und Praxis - Heisler, Dietmar; Lüttke, Daniela (Berufsbildung)

Organisation der dualen Berufsausbildung zum/zur Verkäufer:in und Kaufmann:frau im Einzelhandel im Zeichen der COVID-19-Pandemie. - Sommer, Christian; Szczesny, Daniela (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern.)
One of the most powerful events in the still young 21st century is certainly the outbreak of the coronavirus and the following COVID-19 pandemic. Massive economic as well as social distress caused worldwide devastation. In Germany, not only stores, factories, cultural facilities were closed, but also – for the first time in history – schools were closed nationwide. Closed working sites and vocational schools, as well as working sites, which remained open due to their systemic relevance, led to so far unknown challenges in Germany’s vocational education system. A very good example are the dual apprenticeships, such as trained retail salesman, which were only partially affected by closures. The main goal of education policy was to compensate personal communication and interaction via digital media. This article’s main aim is to reveal the strategies vocational schools have developed to overcome the challenges they had to face because of the pandemic.
Keywords: COVID-19; Digitalization; Vocational education and training; Retail